Penerapan Persamaan Fungsi Linier dalam Menentukan Analisis Break Even Point (BEP) pada UMKM - Puspaningrum, Cici (Sekolah Tinggi Ilmu Ekonomi Bina Karya, 2025)
This study aims to analyze the application of linear function equations in determining the Break Even Point (BEP) for the UMKM Keripik Dewi, serving as a foundation for profit planning and performance evaluation. Using a quantitative descriptive approach, the research processes annual data on sales, fixed costs, and variable costs. The results indicate that linear functions effectively describe the relationship between total costs, revenues, and production volume, enabling accurate BEP calculation in both units and monetary value. The findings show that BEP analysis helps microbusinesses determine minimum production targets, control costs, and anticipate potential losses. Furthermore, this method provides clear insight into the contribution margin required to reach profitability. Overall, the application of linear function models proves to be a simple yet functional analytical tool for UMKM, enhancing accuracy in business planning and operational decision-making.